Final justice - Michaels, Fern (New York, NY : Kensington Books, 2008)
The seven women of the Sisterhood have risked everything in the name of justice, including their own freedom. Their most recent mission promised to reward them with a presidential pardon and a chance to leave their enforced exile. But before they can enjoy their prize, they'll have to tackle a risky new mission in Sin City.
93560
Keywords: Female friendship; Exiles -- United States; Mass media; Adventure fiction